ISSUES OF YOUTH DELINQUENCY PREVENTION - Akhmadjonov Akmaljon (Scholar Express Journals, 2023)
This article is devoted to the study of scientific experiments in the direction of prevention, prevention and reduction of youth delinquency. The causes of youth delinquency and measures to reduce it are researched. Providing legal knowledge to young people, engaging them in sports, creative and scientific activities will help strengthen the fight against youth delinquency. The use of values-based education and giving them work skills play an important role in forming the consciousness and worldview of young people. The article analyzes socio-psychological practice, training manuals and programs and their effectiveness in the prevention of youth delinquency. The issues of prevention of youth delinquency are studied as an actual problem, and proposals are made for ways to solve it
Keywords: youth delinquency; youth delinquency prevention